Surveillance by international institutions. Lessons from the global financial and economic crisis - Shigehara, Kumiharu; Atkinson, Paul (Paris, 2011)
"This paper reviews key policy messages and warnings about developments in the run-up to the global financial and economic crisis that began in mid-2007 which are contained in the main publications of the IMF, the OECD and the BIS and discuss issues relevant to strengthening their surveillance activities for making appropriate policy recommendations and issuing warnings in order to prevent such crisis in the future. The review finds that the institutions did not recognize the need for monetary tightening in a timely way for either the US or the UK, two epicentres of the global crisis. While some concerns were expressed at early stages regarding financial market policies and developments, generally when risks seemed abstract or remote, warnings were too few, received too little emphasis in key editorial sections likely to attract attention and were rarely followed up. Important issues, notably the weak capital base and lack of resilience of the banking systems in the two countries, were missed almost entirely. In the light of this review, suggestions for improving surveillance are offered, relating to (1) strengthening analytical frameworks; (2) improving the current institutional context in which surveillance takes place; (3) staff and management issues; and (4) dissemination and communication. In addition, the need to re-design international frameworks for surveillance to integrate more fully new "major players" in the global economy and financial systems is briefly discussed."